HBD-2 variants and SARS-CoV-2: New insights into inter-individual susceptibility - Behairy, Mohammed Y.; Soltan, Mohamed A.; Eldeen, Muhammad Alaa; Abdulhakim, Jawaher A.; Alnoman, Maryam M.; Abdel-Daim, Mohamed M.; Otifi, Hassan; Al-Qahtani, Saleh M.; Zaki, Mohamed Samir A.; Alsharif, Ghadi; Albogami, Sarah; Jafri, Ibrahim; et al. (Frontiers in Immunology, 2022)
Background A deep understanding of the causes of liability to SARS-CoV-2 is essential to develop new diagnostic tests and therapeutics against this serious virus in order to overcome this pandemic completely. In the light of the discovered role of antimicrobial peptides [such as human b-defensin-2 (hBD-2) and cathelicidin LL-37] in the defense against SARS-CoV-2, it became important to identify the damaging missense mutations in the genes of these molecules and study their role in the pathogenesis of COVID-19. Methods We conducted a comprehensive analysis with multiple in silico approaches to identify the damaging missense SNPs for hBD-2 and LL-37; moreover, we applied docking methods and molecular dynamics analysis to study the impact of the filtered mutations. Results The comprehensive analysis reveals the presence of three damaging SNPs in hBD-2; these SNPs were predicted to decrease the stability of hBD-2 with a damaging impact on hBD-2 structure as well. G51D and C53G mutations were located in highly conserved positions and were associated with differences in the secondary structures of hBD-2. Docking-coupled molecular dynamics simulation analysis revealed compromised binding affinity for hBD-2 SNPs towards the SARS-CoV-2 spike domain. Different protein–protein binding profiles for hBD-2 SNPs, in relation to their native form, were guided through residue-wise levels and differential adopted conformation/orientation. Conclusions The presented model paves the way for identifying patients prone to COVID-19 in a way that would guide the personalization of both the diagnostic and management protocols for this serious disease.